(3QSGdI JejjR GdehMOjf GdWGFYjf ef MRH GdYUGg GdaSbI GdfGcKjfs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi GdEeGe Gdehdi GdEdg GdMGce GdeJYGdi Yf JfRjg GdCfGe hJhSdJ ai GdgOGjI Edjg HYHOg GdbGFe GdgGOi GdEeGe s
(3BNQgG (B:s
(3hgh MSHi hfYe GdfUjQ GdeYjf def Jhcd Ydjg hde jNQL Yf WGYJg hCNdU dg Hbhd Gd UOb JeJ HMeO Gddg Pi GdaUd hGdEMSGf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B65s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds